An empirical investigation the adoption factors of building information modelling (BIM) from the perspective of Malaysian Civil And Structure Consultant Firms - Zahrizan, Zakaria (2021)
The construction industry in the Fourth Industrial Revolution (IR 4.0) have to focus on high-technology jobs such as technological skill rather than labour-intensive approach and low-skilled job. But, most of the construction industries in Malaysia are using traditional approach which is labour-intensive approach and it has resulted in fragmentation issue among the project participants resulting less productivity and inefficiency in delivering the project. In order to tackle this issue, Building Information Modelling (BIM) can offer a platform to integrate between different parties in the construction industry. It also offers a lot of benefits to construction industry in term of productivity and efficiency. Even though there are a lot of benefits that can be gained by BIM utilisation and many efforts to increase the adoption of BIM in construction projects such as conducting the seminars, workshops and incentives but, the rate of BIM adoption by the Malaysian construction players is still low compared to other Asians countries. Therefore, there is a need to study the adoption factors within Malaysian construction industry that could facilitate the pace of BIM adoption in Malaysia especially from the perspective of civil and structure (C&S) consultant firms. Several studies had explored the way to increase the pace of BIM adoption from the perspective of architectures, facilities management, quantity surveyor and contractors, and very little effort to identify the adoption factors and its relationship that could facilitate the adoption of BIM especially from the perspective of C&S consultant firms. C&S consultant firm plays a vital role to ensure the design is constructible, operable and maintainable. Thus, the aim of this study is to examine the relationship between organizations, people and technology towards making decisions in adopting BIM from the perspective C&S consultant firm. In this study, qualitative and quantitative approaches have been utilised as research method to develop in-depth understanding of the happening by obtaining the views on the subject studied especially the current application of BIM in the Malaysian construction industry. At the same time, this study is conducted to explore what are the factors that affecting the adoption of BIM in the Malaysian construction industry. Lack of national guideline for implementing BIM, pressure from clients or governments and lacking of technical support from BIM experts are the vital challenges faced by the adopters besides having a higher cost of early investment in BIM technology. Analysis from multiple linear regression revealed the factors that have a strong relationship in influencing organisation to adopt BIM are; having a strong support from the top management, having a coercive pressure, having a clear BIM implementation plan, undergo training, having a BIM competency team, having a clear job specification for new roles, BIM technology must free from interoperability issue, less cost of technology, and the issue of compatibility. This study offers a new insight from the perspective of C&S consultant firms on the adoption of BIM and could improve the rate of BIM adoption. At the same time, it could fill the gap from previous studies by extending the study of BIM adoption by investigating from C&S consultant firm’s point of view and it complementing the overall view of BIM adoption from all participants.